Coupled Heat and Flow Analysis Inside a Diversion-Type Gas Heater With Vertical Guide Plate Structure - Guo, Yun; Zhang, Xuning; Zhou, Zhongwei (Frontiers in Energy Research, 2022)
The cylinder-type heater with water as intermediate heating medium is most widely employed in the heating process of natural gas. Apparently, the heat exchange rate between the heating medium water and the fire and gas tubes in the large capacity cylinder is the key factor that affects the thermal efficiency of a gas heater. The present paper characterizes water heat flow field inside a new diversion-type gas heater with vertical guide plate structure. Different from previous studies focused on the natural convection heat transfer of the medium water, radiation effect is taken into account. A 2-D combined natural convection and participating medium radiation heat transfer model was built, in which the discrete-ordinate model was used, and solved by the finite volume method with unstructured body-fitted grids. The numerical model was first validated with experimental measurements. Then analyses of the coupled heat flow fields with vertical guide plate of different heights were carried out. The numerical results show that the proportion of the radiation heat transfer in the total heat transfer rate reaches 25.1% by using vertical guide plate structure, which means that the radiation of water cannot be ignored. Using the vertical guide plate structure could form a well-organized flow pattern in the cylinder to enhance natural convection heat transfer, meanwhile have little effect on water radiation. The total heat transfer rate in the convective tube bundle can be reduced by 2.04% via installing a vertical guide plate with a height of 550 mm and thickness of 5 mm. This technology has been granted a patent in China.